2020
DOI: 10.3390/rs12152506
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Analysis of Surface Temperature from Heterogeneous Data in a Maize Field and Related Water Stress

Abstract: Precision agriculture aims at optimizing crop production by adapting management actions to real needs and requires that a reliable and extensive description of soil and crop conditions is available, that multispectral satellite images can provide. The purpose of the present study, based on activities carried out in 2019 on an agricultural area north of Ravenna (Italy) within the project LIFE AGROWETLANDS II, is to evaluate the potentials and limitations of freely available satellite thermal images for the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…NDVI, EVI, and GNDVI are spectral indices widely used for estimating crop biomass [42], assessing plant health status [43,44], and conducting phenological analyses [45,46]. Conversely, NDWI 1-2-3 and NDMI are primarily related to water content and can be used for Ψstem prediction [47][48][49]. No soil-adjusted spectral indices (such as SAVI, OSAVI, MSAVI, or MSAVI2) were considered in this study due to the specific nature of the vineyard.…”
Section: Satellite Datamentioning
confidence: 99%
“…NDVI, EVI, and GNDVI are spectral indices widely used for estimating crop biomass [42], assessing plant health status [43,44], and conducting phenological analyses [45,46]. Conversely, NDWI 1-2-3 and NDMI are primarily related to water content and can be used for Ψstem prediction [47][48][49]. No soil-adjusted spectral indices (such as SAVI, OSAVI, MSAVI, or MSAVI2) were considered in this study due to the specific nature of the vineyard.…”
Section: Satellite Datamentioning
confidence: 99%
“…In those cases, a more complex flight plan should be performed, typically by defining waypoints where the sensor acquisition has to be done [36]. High overlap values near to 60 or even 80% between subsequent images or between tracks are usually applied [28,37].…”
Section: Remote Sensingmentioning
confidence: 99%
“…A remarkable comparative carried out in Italy between free thermal images provided by Landsat-8 satellite and the very high resolution ones obtained by one-hundred-metersheight flights of an UAV is presented in [37]. The study makes use of a four-rotor UAV model Matrice 210 made by DJI that relies on a dual-gimbal configuration to handle the simultaneous use of two sensors' payloads.…”
Section: Water Stress Analysismentioning
confidence: 99%
“…Crop water management is essential in regions currently facing or predicted to face water scarcity. Infrared thermography has been successfully implemented to assess water use by crops ( Nhamo et al, 2020 ), and for measuring genotype performance under salinity or water deficit stress ( Raza et al, 2014 ; Kumar et al, 2017 ; Thapa et al, 2018 ; Hou et al, 2019 ; Zhang et al, 2019b ; Kumar et al, 2020 ; Masina et al, 2020 ). In cotton ( Gossypium arboreum ) monitored by infrared thermography, it was observed that yield, fiber length, and micronaire suffered reduction after canopy temperature exceeded a given threshold ( Conaty et al, 2015 ).…”
Section: Applications Of Htpmentioning
confidence: 99%